Asymmetry during landing impacts following jumps with aerial rotation in collegiate men's basketball players - Harry, J. R.; Park, S.; Stewart, M.; Hite, M.; Simms, A.; Larsen, M.; Bishop, C. (The Journal of Strength and Conditioning Research, 2025)
This project explored whether (a) landing performances and (b) impact force asymmetries were different during countermovement jump (CMJ) landings with leftward versus rightward aerial rotation in 19 collegiate men's basketball players. Replicated single-subject analyses were performed to identify differences that were both statistically significant and important for each individual. Countermovement jump landing performance and loading, attenuation, and control phase durations were compared, while interlimb vertical ground reaction forces (GRF) were compared during each phase of CMJ landings with leftward and rightward rotations, respectively, using the model statistic and coefficient of variation techniques. The model statistic provided random chance probability (a = 0.05). The coefficient of variation provided whether differences exceeded the largest amount of variation from each limb or rotation direction. The bilateral asymmetry index (BAI; difference between dominant and nondominant limbs divided by the sum of the 2 limbs) was also calculated. Statistically significant (model statistic results) and important (coefficient of variation results) differences in landing performance were detected between rotation conditions in 4 subjects. Most subjects did not display significant and important asymmetries for the changes of vertical GRF during any phase of CMJ landings with leftward or rightward rotations. Large amounts of intra-individual variation seem to be an influential factor for these results, as basketball players seem to have unrefined landing strategies that could require targeted training. Because the BAI values reached as high as ± 531% without coinciding with significant and important asymmetry, researchers and practitioners may need to reevaluate the way in which asymmetry indices are interpreted.